Penciptaan Busana Art of Beat Style Menggunakan Teknik Fabric Thread Collage - Bidayatunnisa’i Bidayatunnisa’i; Fadri Rahmat; Desi Trisnawati; Desra Imelda (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This work, titled "Art of Beat Style with Fabric Thread Collage," is inspired by the freedom of contemporary visuals manifested in eccentric, artistic, and antimainstream fashion concepts. The garments are designed with dynamic asymmetrical cuts to challenge mainstream mass trends. The Art of Beat concept is visualized on the fabric surface through rich textural plays and striking, contrasting color combinations. The creator integrates Batik Truntum from Surakarta to elevate local elements and the deep philosophical meanings of tradition combined  into contemporary fashion. The color palette selection employs bold and clashing hues, namely red, yellow, pink, blue, and turquoise. The materials used in this collection include woolpeach, toyobo, texas, drill, organza, tulle, woolen threads, and Batik Truntum as the combination fabric. The creation method begins with the preparation (exploration) stage, which involves field surveys through visual observations of international designers' fashion show videos, literature reviews to gather relevant theoretical foundations, and formulating visual design ideas through moodboard compilation. The primary techniques utilized in this work are fabric thread collage (fabric surface manipulation using free-motion stitching), double-edged ruffle technique, flounce technique, and pearl bead embellishments. The final realized collection consists of three tiers of fashion lines: ready-to-wear titled (The Beat Play), ready-to-wear deluxe, and haute couture.